Initial stages of attitude’s instrument adaptation to brazilian sports competitions - Hirota, Vinicius Barroso; Diniz, Denis Victor; Silva, Marcel Rodrigo da; Lima, Rafael Oliveira de; Verardi, Carlos Eduardo Lopes [UNESP]; Marco, Ademir de (My University, 2014)
The aim of this study was to adapt and initiate validation of an instrument of attitudes toward mathematics to sports competitions. So through a correlational study, we adapted the instrument counting on a total sample of 260 young athletes (n=260), all students, divided into three rounds, and the confirmatory purpose we apply a pre competitive stress scale in order to show mappable symptoms. An initial reliability of the instrument, Alpha 0.83 to negative attitudes, and 0.90 for positive attitudes, with the average results of 2.52 (±0.86) to negative attitudes and 4.66 (±0.84) was determined for attitudes positive; we conclude that the instrument performed well in this first test, and should be applied in a larger sample, by un mounting this case study that young athletes have positive attitudes toward sports competition, so they enjoy participating in the competition.
Keywords: Sports competitions; Instrument; Attitudes; Assessment